2015
DOI: 10.1093/ije/dyv194
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology ofMycoplasma genitaliumin British men and women aged 16–44 years: evidence from the third National Survey of Sexual Attitudes and Lifestyles (Natsal-3)

Abstract: Background: There are currently no large general population epidemiological studies of Mycoplasma genitalium (MG), which include prevalence, risk factors, symptoms and co-infection in men and women across a broad age range.Methods: In 2010-–12, we conducted the third National Survey of Sexual Attitudes and Lifestyles (Natsal-3), a probability sample survey in Britain. Urine from 4507 sexually-experienced participants, aged 16–44 years, was tested for MG.Results: MG prevalence was 1.2% [95% confidence interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
114
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(134 citation statements)
references
References 28 publications
15
114
0
5
Order By: Relevance
“…Other studies have reported higher rates of MG in non-Caucasian populations 20 21. Our finding of disproportionately high rates of MG among Indigenous persons is in keeping with the higher estimated STI prevalence in Canadian Indigenous persons when compared with the overall general population 22 23.…”
Section: Discussionsupporting
confidence: 85%
“…Other studies have reported higher rates of MG in non-Caucasian populations 20 21. Our finding of disproportionately high rates of MG among Indigenous persons is in keeping with the higher estimated STI prevalence in Canadian Indigenous persons when compared with the overall general population 22 23.…”
Section: Discussionsupporting
confidence: 85%
“…Recent studies suggest that many patients are unaware of their M. genitalium infection. For example, Manhart et al (22) found that none of the M. genitalium-positive patients enrolled in the U.S. general population-based AddHealth study reported symptoms of vaginal or urethral discharge, and in a British national survey study, Sonnenberg et al (23) determined that 94% of men and 56% of women infected with M. genitalium were asymptomatic.…”
mentioning
confidence: 99%
“…Most infections are probably asymptomatic and have no adverse health outcomes 34. Nonetheless, evidence that M genitalium is associated with serious genitourinary and reproductive health morbidity is accumulating.…”
mentioning
confidence: 99%
“…In Britain, a probability sample survey estimated a prevalence of around 1.3% in the sexually active British population aged 16-44 years 4. In common with many other sexually transmitted infections (STIs), M genitalium infection rates can be considerably higher in men who have sex with men, sex workers, and people attending STI clinics,11 but those infected tend to be older than people with other STIs such as chlamydia; 91% of infected men and 67% of infected women are aged 25 to 44 4…”
mentioning
confidence: 99%